2018
DOI: 10.1002/cche.10047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different lipases on bread staling in comparison with Diacetyl tartaric ester of monoglycerides (DATEM)

Abstract: Background and objectives Lipases are applied in breadmaking as an enzymatic replacement for typical bakery surfactants like Diacetyl tartaric ester of monoglycerides (DATEM) (diacetyl tartaric ester of monoglycerides). In this study, the influence of six commercially available lipases and DATEM on bread staling and bread height was investigated. Therefore, a microbaking experiment was conducted, where 15 g of dough was used for each bread. Microbaking breads were analyzed for height, baking loss, and crumb fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Section 6.2) (Krog, 1981). Lipases have logically been proposed to be (partial) alternatives for surfactants in bread making as they increase the polarity of the endogenously present lipid population by liberating one or more FA(s) from (non)polar lipids ( Figure 12) (Colakoglu & Özkaya, 2012;Frauenlob et al, 2018;Moayedallaie et al, 2010). For more information on surfactants and their role in bread making, the interested reader is referred to the reviews of Stampfli and Nersten (1995) and Pareyt et al (2011).…”
Section: Exogenous or Added Lipids In Bread Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Section 6.2) (Krog, 1981). Lipases have logically been proposed to be (partial) alternatives for surfactants in bread making as they increase the polarity of the endogenously present lipid population by liberating one or more FA(s) from (non)polar lipids ( Figure 12) (Colakoglu & Özkaya, 2012;Frauenlob et al, 2018;Moayedallaie et al, 2010). For more information on surfactants and their role in bread making, the interested reader is referred to the reviews of Stampfli and Nersten (1995) and Pareyt et al (2011).…”
Section: Exogenous or Added Lipids In Bread Makingmentioning
confidence: 99%
“…It increases the stability and maximum resistance to extension of dough while decreasing its stickiness (Colakoglu & Özkaya, 2012). Furthermore, lipase action in bread making increases LV (Aravindan, Anbumathi, & Viruthagiri, 2007; De Maria et al., 2007; Frauenlob, Scharl, D'Amico, & Schoenlechner, 2018; Gerits et al., 2014; Gerits, Pareyt, Masure, et al., 2015b; Melis, Meza Morales, et al., 2019; Melis, Verbauwhede, et al., 2019; Moayedallaie, Mirzaei, & Paterson, 2010) improves crumb softness and structure (Aravindan et al., 2007; Poulson, Søe, Rasmussen, Madrid, & Zargahi, 2010) and delays or even reduces the extent to which starch retrogradation occurs during storage (Colakoglu & Özkaya, 2012; Frauenlob et al., 2018; Gerits, Pareyt, Masure, et al., 2015a; Siswoyo, Tanaka, & Morita, 1999). In this context, lipases have logically been proposed to be (partial) alternatives for surfactants in bread making as they in situ produce molecules with a hydrophilic head and a hydrophobic tail resembling surfactants (Aravindan et al., 2007; Colakoglu & Özkaya, 2012; De Maria et al., 2007; Moayedallaie et al., 2010).…”
Section: Wheat Endogenous Lipids In Bread Making: Impact On Quality Omentioning
confidence: 99%
“…The starch lipids are essentially unavailable due to their location inside the granular structure (De Maria, Vind, Oxenbøll, Svendsen, & Patkar, 2007). Lipases improve dough processing as well as overall bread quality by increasing dough stability, maximum resistance to extension and hardness, decreasing dough stickiness, increasing specific LV, improving crumb softness and structure and delaying retrogradation during storage (Aravindan, Anbumathi, & Viruthagiri, 2007;Colakoglu & Özkaya, 2012;De Maria, et al, 2007;Frauenlob, Scharl, D'Amico, & Schoenlechner, 2018;Gerits, et al, 2014;Gerits, et al, 2015;Moayedallaie, Mirzaei, & Paterson, 2010). It has also been suggested that lipases can partially or completely replace surfactants in BM as they in situ generate surfactant-like molecules by hydrolyzing wheat endogenous lipids (Aravindan, et al, 2007;Colakoglu, et al, 2012;De Maria, et al, 2007;Moayedallaie, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While, the lipase and lipoxygenase activities determine the poor and unstable sensory properties of baked goods made of wheat flour containing the germ ( Paradiso et al, 2008 ). However, lipases are sometimes used in bakery industry as emulsifiers to increase the bread volume, soften the crumb as well as retarding bread staling ( Frauenlob et al, 2018 ). Thermal treatments can be used to inactivate the enzymes, however, collateral negative effects on the bioactive compounds, i.e., destruction of essential fatty acids and vitamins are often highlighted ( Sjovall et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%